Aerodynamics profile not in stationary flow - Загорулько, А.А.; Швець, О.В. (Proceedings of National Aviation University, 2006)
Consider the question about influence of unsteady flight on the size of drag and lift coefficients of theaerodynamic profile. Distinctive features of this investigation are obtaining data about aerodynamic drag chancing in process unsteady on high angle at attack and oscillation profile in subsonic and transonic flight. Given analysis of oscillation profile show, that dynamic loops accompany change of lift and dray force. The researches show that it is necessary to clarity the mathematic model of the airplane flight dynamics by introducing numbers, with take into account unsteady effects.